Dynamic linkages between energy efficiency, renewable energy along with economic growth and carbon emission. A case of MINT countries an asymmetric analysis - Rabia Akram; Muhammad Umar; Gan Xiaoli; Fuzhong Chen (Energy Reports, 2022)
This study aims to examine the effects of energy efficiency (EE), renewable energy (RE), and other factors on the carbon emissions of Mexico, Indonesia, Nigeria, and Turkey (MINT). The study covers the time from 1990 to 2014. Unlike earlier studies, the current analysis considers EE a significant factor of CO2 emissions in the MINT nations. MINT primarily represents a group of emerging economies, but it is relatively ignored in empirical environment literature. The mitigating effect of EE on CO2 emissions in the MINT nations has not been explored before. This study is the first to reveal an asymmetric connection among EE, RE, nuclear energy, economic growth, and CO2 emissions in the MINT nations by using the novel hidden panel cointegration and nonlinear panel autoregressive distributive lag methodology. The empirical results suggest that the variables’ effects are asymmetric, and EE and RE reduce the carbon emissions in the MINT countries. In the case of EE, a 1% fluctuation in its positive-sum lowers carbon emissions by 0.232% in the long term, and a 1% fluctuation in its positive-sum mitigates CO2 pollutants by 0.112% in the short term. For RE, a 1% fluctuation in its positive component lowers carbon emissions by 0.846%. Furthermore, findings from the Granger causality test suggest that any reductions in EE would have a positive impact on the extent of carbon emissions. The permanent positive shocks of EE show a negative association with carbon emissions. On the basis of these empirical findings, this study suggests that policy managers of the MINT countries should consider the asymmetric behavior among the variables in setting their environmental, growth, and energy policies.